2019
DOI: 10.1016/j.jobe.2019.100883
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a sequential versus holistic building design approach using multi-objective optimization

Abstract: Integrated design processes are currently pushed forward in order to achieve net-zero energy building designs at affordable cost. Through a case study of a residential building, this paper compares a sequential versus a holistic design approach based on multi-objective optimization. In the holistic approach, 39 design variables related to the architecture and HVAC systems are simultaneously optimized. In the sequential approach, the architecture variables are first optimized; several optimal solutions are then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Holistic integrated design and performance optimization are not commonly considered at preliminary stages [55], where early design of buildings is often shaped by engineering intuition, designer prior experience, and project's economic constraints. A past survey showed that early decisions on building geometry and orientation are impacted by site location and zoning ordinances, whereas decisions on structural and envelope systems are influenced by project pricing [24].…”
Section: Early Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Holistic integrated design and performance optimization are not commonly considered at preliminary stages [55], where early design of buildings is often shaped by engineering intuition, designer prior experience, and project's economic constraints. A past survey showed that early decisions on building geometry and orientation are impacted by site location and zoning ordinances, whereas decisions on structural and envelope systems are influenced by project pricing [24].…”
Section: Early Designmentioning
confidence: 99%
“…A past survey showed that early decisions on building geometry and orientation are impacted by site location and zoning ordinances, whereas decisions on structural and envelope systems are influenced by project pricing [24]. Among the limited efforts, Gagnon et al compared holistic and sequential design for a residential building using 39 design variables (mostly associated with envelope system) and three objectives of cost, thermal comfort and greenhouse gas emission [55]. Bernett et al developed an early design decision-making framework to generate schematic designs that are ranked based on energy use, embodied carbon [56].…”
Section: Early Designmentioning
confidence: 99%
“…Gagnon et al [33] compared the computational resources spent in sequential and holistic approaches of a net-zero building design, using NSGA-II to optimize the carbon footprint, lifecycle cost, and thermal comfort. The experiment proved that the holistic approach achieved 59% of the optimal solutions in 100 h, and the sequential approach achieved 41% in 765 h.…”
Section: Research Activitymentioning
confidence: 99%
“…Various control strategies ranging from rule-based to the use of artificial neural networks (ANN) methods of toggling between GHEs and the available alternatives resulted in significant COP improvements for these systems [165,166].…”
Section: State Of the Artmentioning
confidence: 99%
“…The uncovering of 4.3. Description of the chosen case study counter-intuitive operating strategies which could only have resulted through the modeling of the tight-coupling between the main components and ancillaries of the system are clearly illustrated in [166].…”
Section: State Of the Artmentioning
confidence: 99%